2007
DOI: 10.1002/jso.20740
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 mRNA expression correlates with aromatase expression in human breast cancer

Abstract: This study demonstrates a strong positive relationship between COX-2 and aromatase mRNA expression, and lends further support to the hypothesis that COX-2 is an upregulator of aromatase in breast tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Besides finding an increased effect on estrogen synthesis in malignant breast tissue, a strong correlation between COX-2 and aromatase mRNA expression were found. This data supports the assumption that COX-2 is able to regulate aromatase activity in breast tissue [92]. A possible synergism between COX-2 and aromatase-inhibitors is even more interesting and so a prospective randomised phase III multicenter trial (REACT-trial) was conducted that included primary breast cancer patients in order to evaluate the combination of celecoxib and exemestane, an aromatase inhibitor, in an adjuvant setting.…”
Section: Cox-2-inhibitors In Systemic Treatmentsupporting
confidence: 58%
See 1 more Smart Citation
“…Besides finding an increased effect on estrogen synthesis in malignant breast tissue, a strong correlation between COX-2 and aromatase mRNA expression were found. This data supports the assumption that COX-2 is able to regulate aromatase activity in breast tissue [92]. A possible synergism between COX-2 and aromatase-inhibitors is even more interesting and so a prospective randomised phase III multicenter trial (REACT-trial) was conducted that included primary breast cancer patients in order to evaluate the combination of celecoxib and exemestane, an aromatase inhibitor, in an adjuvant setting.…”
Section: Cox-2-inhibitors In Systemic Treatmentsupporting
confidence: 58%
“…For example, COX-2 expression is correlated with the expression of the aromatase [92] and in vitro studies support this data. It has been shown that COX-2 promotes the aromatase transcription, whereas COX-2 inhibitors diminish it [93].…”
Section: Cox-2 and Hormone Receptorsmentioning
confidence: 67%
“…Expression of aromatase leads to oestrogen production, and from cell line studies, we know that hormone receptor expression can be induced by sex steroid hormones [48][49][50][51]. We have recently reported a highly significant correlation between COX-2 and aromatase mRNA expressions in human breast cancer [52]. These findings provide a speculative basis for the correlations observed between COX-2 and hormone receptor expression.…”
Section: Subsets Of Breast Cancer Which Are Hormone Receptor Positivementioning
confidence: 86%
“…COX-2 is responsible for the conversion of arachidonate into PGE 2 , which can increase estrogen production in malignant breast tissue by cAMP-pathway mediated up-regulated expression of aromatase, and estrogen/estrogen receptor complex can be transferred into nucleus to function as an activator to promote the proliferation of estrogen-dependent mammary carcinoma cells (Salhab et al 2007;Brueggemeier et al 2005Brueggemeier et al , 2007. Collectively, we think that the relationship between the development of MCF-7 xenograft tumors and the levels of PUFAs and steroid hormone can be depicted as Fig.…”
Section: Dysregulated Metabolic Pathway Of Mcf-7 Xenograft Micementioning
confidence: 99%